Analisis Empiris Perilaku Perjalanan Wisata Berbasis Kota Populer Media Sosial - Angelia Putriana (TOBA: Journal of Tourism, Hospitality, and Destination, 2026)
Social network information has become a decisive factor in travel decision making alongside the emergence of internet celebrity cities and key opinion leaders, yet the mechanism through which information sources and information quality shape both travel intention and actual travel behavior remains insufficiently understood. This study aims to reveal the psychological transmission mechanism of social network information on travel intention and travel behavior by integrating the Stimulus Organism Response theory, the theory of planned behaviour, and the technology acceptance model into an integrated choice and latent variable (ICLV) model. A quantitative survey was conducted across six popular destinations in two prominent cities, yielding 522 valid responses that were analyzed using structural equation modeling and ICLV model calibration. The results indicate that the information quality of key opinion leaders is the most dominant stimulus for travel motivation with a coefficient of 0.588, travel attitude is the strongest predictor of travel intention at 0.741 while serving as the primary mediator, and destination image and information quality form a parallel rather than a linear relationship in stimulating tourists' psychological organism. The ICLV model outperforms the conventional binary logit model, with the coefficient of determination rising from 0.2649 to 0.4185 and the hit rate improving from 74.27 percent to 85.25 percent. These findings bridge the cognitive separation between intention and action and provide a strategic foundation for destination marketing in the digital era.